Terminological subset of the International Classification for Nursing Practice for institutionalized elderly people (Revista Científica Integrada, 2023)
Aim: To build a terminological subset of the International Classification for Nursing Practice (ICNP®) for institutionalized elderly people, based on Virginia Henderson's Theory of Fundamental Human Needs (NHF). Methods: Methodological study, following the steps: mapping of the Nursing Diagnoses/Outcomes (ND/NO) with the pre-coordinated concepts of the ICNP® version 2017; construction of operational definitions of ND/RE concepts; validation by consensus of the ND/RE concepts and their respective operational definitions; construction and validation of Nursing Interventions (IE) for each validated ND/NO; structuring of the terminological subset. Results: 133 ND/RE and 1474 IE concepts were validated, most of which were classified in the Biological/Physiological Component, for the terminological subset for institutionalized elderly people. Conclusion: It is expected that the constructed terminological subsets can serve as an easily accessible reference for the nurse and favor comprehensive care for the elderly in Long Stay Institutions for the Elderly.
Keywords: Elderly; Long Stay Institution for the Elderly; Nursing Process; Standardized Nursing Terminology; Classification